The Ghost in the Touchscreen: Social Scaffolds Promote Learning by Toddlers. - Zimmermann, Laura; Moser, Alecia; Lee, Herietta; Gerhardstein, Peter; Barr, Rachel (Child Development)
This study examined the effect of a "ghost" demonstration on toddlers' imitation. In the ghost condition, virtual pieces moved to make a fish or boat puzzle. Fifty-two 2.5- and 3-year-olds were tested on a touchscreen (no transfer) or with 3D pieces (transfer); children tested with 3D pieces scored above a no demonstration baseline, but children tested on the touchscreen did not. Practice on the touchscreen (n = 23) by 2.5- and 3-year-olds prior to the ghost demonstration did not improve performance. Finally, children who learned the puzzle task via a social demonstration and were tested on the touchscreen (n = 26) performed better than the ghost conditions. Taken together, these studies demonstrate that social demonstrations enhance learning from novel touchscreen tools during early childhood.